2021
DOI: 10.3947/ic.2021.0008
|View full text |Cite
|
Sign up to set email alerts
|

Ceftriaxone and Doxycycline induced Seroconversion in Previously Seronegative Patient with Clinically Suspected Disseminated Lyme Disease: Case Report

Abstract: We present a case of middle-aged woman whose health problems began 3 months after a registered tick bite in endemic area of Lyme borreliosis. First symptoms included fatigue, chills, cervical lymphadenopathy, neck pain and stiffness. Patient was afebrile. Lyme disease was excluded due to lack of erythema migrans and negative enzyme immunoassay test results for anti- Borrelia antibodies. During the next few months, her condition was getting worse and symptoms were accompanied with brain f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…At both T0 and T2, serologically negative patients had abnormal clinical markers ( Figure 2 and Table 3 ). Other studies have also demonstrated that patients with TBIs may have delayed or no seroconversion [ 22 , 26 , 27 ]. TBIs can cause immune dysfunction that might prevent an effective B cell response [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At both T0 and T2, serologically negative patients had abnormal clinical markers ( Figure 2 and Table 3 ). Other studies have also demonstrated that patients with TBIs may have delayed or no seroconversion [ 22 , 26 , 27 ]. TBIs can cause immune dysfunction that might prevent an effective B cell response [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Current methods to diagnose Lyme disease and other TBIs can be insufficient [ 11 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Lyme disease diagnosis is supported by patient history, clinical examination findings, and completing serology tests [ 11 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although serology remains the mainstay of diagnosis, of seronegative Lyme disease has been reported. Moreover, persistent disease has been observed, despite prompt antibiotic treatment in patients who have become seronegative in response to treatment [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serologic Lb diagnostics are further complicated by variation in the human adaptive immune response. If patients are diagnosed with Lb based on an EM rash and antibiotic treatment is promptly initiated, they might not seroconvert [ 181 , 182 ]. This fact further complicates the surveillance and confirmation of Lb.…”
Section: Borreliaceae Diagnosticsmentioning
confidence: 99%